Revising Incidence and Mortality of Lung Cancer in Central Europe: An Epidemiology Review From Hungary - Bogos, Krisztina; Kiss, Zoltán; Gálffy, Gabriella; Tamási, Lilla; Ostoros, Gyula; Müller, Veronika; Urbán, László; Bittner, Nóra; Sárosi, Veronika; Vastag, Aladár; Polányi, Zoltán; Nagy-Erdei, Zsófia; et al. (Frontiers in Oncology, 2019)
Objective: While Hungary is often reported to have the highest incidence and mortality rates of lung cancer, until 2018 no nationwide epidemiology study was conducted to confirm these figures. The objective of this study was to estimate the occurrence of lung cancer in Hungary based on a retrospective review of the National Health Insurance Fund (NHIF) database. Methods: Our retrospective, longitudinal study included patients aged ≥20 years who were diagnosed with lung cancer (ICD-10 C34) between 1 Jan 2011 and 31 Dec 2016. Age-standardized incidence and mortality rates were calculated using both the 1976 and 2013 European Standard Populations (ESP). Results: Between 2011 and 2016, 6,996 to 7,158 new lung cancer cases were recorded in the NHIF database annually, and 6,045 to 6,465 all-cause deaths occurred per year. Age-adjusted incidence rates were 115.7–101.6/100,000 person-years among men (ESP 1976: 84.7–72. 6), showing a mean annual change of -2.26% (p=0.008). Incidence rates among females increased from 48.3 to 50.3/100,000 person-years (ESP 1976: 36.9–38.0) (mean annual change of 1.23%; p=0.028). Age-standardized mortality rates varied between 103.8 and 97.2/100,000 person-years (ESP 1976: 72.8–69.7) in men and between 38.3 and 42.7/100,000 person-years (ESP 1976: 27.8–29.3) in women. Conclusion: Age-standardized incidence and mortality rates of lung cancer in Hungary were found to be high compared to Western-European countries, but lower than those reported by previous publications. The incidence of lung cancer decreased in men, while there was an increase in incidence and mortality among female lung cancer patients.